Bioactivity Diversity in Coriander Sativum: A Comprehensive Review (International Journal of Food and Nutritional Sciences, 2022)
Coriander Sativum, commonly known as coriander or cilantro, is an aromatic herb extensively used in culinary and traditional medicine practices worldwide. This review paper aims to provide a comprehensive overview of the bioactivity diversity exhibited by Coriander Sativum, focusing on its various phytochemical constituents and their potential medicinal properties. The vast range of bioactive compounds found in Coriander Sativum includes essential oils, phenolic compounds, flavonoids, alkaloids, and terpenes, among others. These bioactive compounds have been extensively investigated for their antioxidant, antimicrobial, anti-inflammatory, anti-diabetic, anticancer, and neuroprotective activities. Moreover, this review also highlights the potential therapeutic applications of Coriander Sativum in the management and prevention of various diseases. The aim of this paper is to consolidate the existing knowledge on the bioactivity diversity of Coriander Sativum and provide insights into its potential as a natural source of bioactive compounds for pharmaceutical and nutraceutical